+0  
 
0
221
1
avatar

H(x)=(x^2)+1 and K(x)=-(x^2)+4. If K(H)=0, what are the roots/solutions?

Guest May 24, 2017
 #1
avatar+87301 
+2

 

K(H)  =  - ( x^2 + 1)^2 + 4  ....so

 

-(x^2 + 1)^2  + 4  = 0      

 

-(x^2 + 1)^2   = -4   multiply through by -1

 

(x^2 + 1)^2   = 4     take the pos/neg square roots

 

x^2 + 1  =  ± 2

 

So...either

 

x^2 + 1  = 2          subtract 1 from both sides

 

x^2  = 1         take both square roots

 

x = ± 1

 

Or

 

x^2 + 1  = -2    subtract 1 from both sides

 

x^2  =   -3    take both square roots

 

x = ± (√3) i

 

And those are the 4 solutions

 

 

 

cool cool cool

CPhill  May 24, 2017
edited by CPhill  May 24, 2017

11 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.